In the beauty of the lilies - Updike, John. (New York : A.A. Knopf, 1996)
John Updike's seventeenth novel begins in 1910, and traces God's relation to four generations of an American family, beginning with Clarence Wilmot, a Presbyterian clergyman in Paterson, New Jersey. He loses his faith, and becomes an encyclopedia salesman and a motion-picture addict. The remainder of Clarence's family moves to the small town of Basingstoke, Delaware, where his cautious son, Teddy, becomes a mailman. Faithless himself, Teddy marries a good Methodist girl and begets Esther, whose prayers are always answered; she becomes an object of worship, a twentieth-century goddess. Her neglected son, Clark, makes his way back to the fiery fundamentals of Protestant piety. The novel ends in 1990, in Lower Branch, Colorado, and on television. Taking its title from the "Battle-Hymn of the Republic," In the Beauty of the Lilies spins one saga, one wandering tapestry thread, of the American Century.
Keywords: Clergy -- Fiction; Cults -- Fiction; Religious fiction; Domestic fiction